Etnobiologia de uma comunidade ribeirinha no Alto da Bacia do Rio Aricá Açu, Cuiabá, Mato Grosso, Brasil - Pasa, Maria Corette (Universidade Federal de São Carlos, 2004)
This study was carried out in a rural community Conceição-Açu located in the country of Cuiaba, Mato Grosso state. The main purpose of this paper was to interpret the existent relationship between the population and their environment, inserted in the socio cultural and environment context related to the use of vegetal plants and animal resources. Through the information given, it was possible to analyse the social structure and the quality of life of the people in the region and identify the different ways of using the natural resources and the knowhow the population has about the environment through the techniques used in the conservation process. The method used combined qualitative and quantitative aspects when putting into practice the following stages: ecological description of the ecosystems; socio economical description of the families involved in this study, a follow up of the main productive activities and also of the activities of collecting in the gallery woods; Checking of the different strategies used in the preparation and conservation of the vegetal plant resources and the interpretation of the etnobiological knowledge, giving emphasis to the etnobotanic and etnozoologic aspect, given by yhe local population. The rural inhabitants identify several micro habitas in the interior of the gallery wood, to which the presence of certain species of vegetal plants and animals are associated. People showed a comprehensive understanding of the trophic and reprodutive behaviour of the animals that they know and live with in their properties and in nearby areas, not forgetting the ecological association plant-animal-plant. It s attributed to the plants (suffer more or less; react a lot or react a little) and to the animals (eat a lot or a little, they are wild or tame) a classification by bynary opposition because of their behaviour. Starting from the etnoknowledge that the local population showed about the use of the natural resources it was possible to make the comparison with the scientific knowledge, through tables, aiming at showing the agreement between both interpretation about the ecosystem and its natural resources. The value of use of the vegetal plant species revealed and interaction of the people with the environment, pointing to the relevence of the gallery wood for the storage of renewable natural resources. The economic exploitation in the region has a small environment impact, favoring, in this way the conservation of the local flora and fauna.
Keywords: Ecologia humana; Recursos vegetais; Etnobiologia; Mata ciliar; Conservação; Vegetal plants resources; Etnobiological; Gallery Wood; Conservation; CIENCIAS BIOLOGICAS::ECOLOGIA